PELAKSANAAN PENDIDIKAN ISLAM AHLUS SUNNAH WAL JAMAAH DI SMP WAHID HASYIM DINOYO KOTA MALANG - M. Agus Isnaini; M. Ilyas Thohari; Syamsu Madyan (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
In the midst of the development of science and technology in Indonesia in general is very influential on the existence and role of Islamic education in Indonesia, Islamic education is encouraged to continue to be able to provide answers to the development of the times. the formation of character is hampered because it is felt unable to compensate for moral changes that occur in society due to the negative influence of the development of science and technology, therefore the Islamic education of Ahlus Sunnah wal Jama'ah is present as an answer to compensate and anticipate it, although various efforts will continue to be made. The Islamic Education of Ahlus Sunnah wal Jama'ah which upholds the values of tawasut, tasamuh, tawazun and ta'dul is considered sufficient to answer the various challenges in this era. Cultivation of character through these values is characteristic for educational institutions under the auspices of the Nahdlatul Ulama, so the results can contribute to the community in shaping characters that are in accordance with these values.